The Relationship Between Diet Patterns and Sleep Quality with the Occurrence of Acne Vulgaris in Students of the State Islamic University of North Sumatra Tuntungan - Rangkuti, Azkyatul Arifah; Siahaan, Nur Latipah; Aryulika, Mawar; Utami, Dilla Fitri; Wahyudi, Wahyudi (Universitas Ibn Khaldun Bogor, 2025)
Acne (Acne vulgaris) is a common chronic skin disorder, in which diet and sleep quality are suspected as risk factors. This study aims to analyze the relationship between diet and sleep quality with the appearance of acne in UINSU Tuntungan students. This study used a case-control design with a quantitative approach, involving 80 respondents selected by stratified random sampling. Data were collected through questionnaires and analyzed using the Chi-square test at a significance level of 5%. The results showed that 82.5% of respondents had a good diet and 60% had good sleep quality. However, there was no significant relationship between diet (p = 0.378) or sleep quality (p = 0.494) with the appearance of acne. Although there was a tendency for acne to appear more in respondents with poor diet and sleep patterns, it was not statistically significant. Therefore, understanding the causes of acne requires a more comprehensive approach.